2013
DOI: 10.1590/s0100-54052013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Etiologia e quantificação dos agentes causais de manchas foliares na cultura do trigo nas safras 2008 a 2011

Abstract: RESUMOPalavras-chave adicionais: Triticum aestivum, Drechslera, Bipolaris, Stagonospora, ocorrência.T he whea t (Tritic u m a e stiv u m L.) crop is one of the most importa nt options for cultiva tion in the winter sea son. Among the foliar diseases, yellow leaf spot, brown-spot and septoriosis, are cited as the most frequent leaf spot in wheat. This study aimed to identify and quantify the pathogenic fungi associated with leaf spot symptoms in wheat cultivars in Regions of Value for Cultivation and Use (RVCU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…tritici (Tonin et al, 2013), while reductions in sensitivity to strobilurins (QoIs) were reported for the wheat yellow leaf spot pathogens Drechslera siccans and Drechslera tritici-repentis (Tonin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…tritici (Tonin et al, 2013), while reductions in sensitivity to strobilurins (QoIs) were reported for the wheat yellow leaf spot pathogens Drechslera siccans and Drechslera tritici-repentis (Tonin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These transition areas make up a complex system, which is not yet well understood, which involves the cycling of nutrients between soil-plant-animal. Deforestation and lack of diversity of cultures may result in an unsustainable system, characterised by progressive soil degradation due to the emergence of pests and diseases in agricultural areas (Alves et al, 2011;Santos et al, 2012;Tonin et al, 2013), high production costs and resistance of pathogens to fungicides (Xiao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From 2004 season, farmers and farm advisers have complained about the difficulty in controlling wheat leaf blights by using fungicides. Some authors (11,12) have shown that the reduced sensitivity of Drechslera spp. to strobilurins and triazoles, except for pyraclostrobin, may explain the control failure.…”
Section: Introductionmentioning
confidence: 99%